2022
DOI: 10.3390/pharmaceutics14061269
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole-Curcumin Suppresses Cardiomyocyte Hypertrophy by Disrupting the CDK9/CyclinT1 Complex

Abstract: The intrinsic histone acetyltransferase (HAT), p300, has an important role in the development and progression of heart failure. Curcumin (CUR), a natural p300-specific HAT inhibitor, suppresses hypertrophic responses and prevents deterioration of left-ventricular systolic function in heart-failure models. However, few structure–activity relationship studies on cardiomyocyte hypertrophy using CUR have been conducted. To evaluate if prenylated pyrazolo curcumin (PPC) and curcumin pyrazole (PyrC) can suppress car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Acetylation of H3K9 and H3K27 has also been suggested to be involved in the expression of GATA4, as GATA4 is involved in the development of HF and the fetal gene is reactivated during HF, suggesting that the acetylation of H3K4 may be involved in cardiac hypertrophy and HF ( 25 , 26 ). Many reports have suggested that the acetylation of H3K9 by p300 causes cardiomyocyte hypertrophy ( 3 , 4 , 27 30 ). Furthermore, H3K9 acetylation is increased during cardiac hypertrophy and HF in TAC and Dahl rats ( 4 , 26 , 31 ).…”
Section: Histone Acetylation In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
See 3 more Smart Citations
“…Acetylation of H3K9 and H3K27 has also been suggested to be involved in the expression of GATA4, as GATA4 is involved in the development of HF and the fetal gene is reactivated during HF, suggesting that the acetylation of H3K4 may be involved in cardiac hypertrophy and HF ( 25 , 26 ). Many reports have suggested that the acetylation of H3K9 by p300 causes cardiomyocyte hypertrophy ( 3 , 4 , 27 30 ). Furthermore, H3K9 acetylation is increased during cardiac hypertrophy and HF in TAC and Dahl rats ( 4 , 26 , 31 ).…”
Section: Histone Acetylation In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%
“…Acetylation of histones by p300 is involved in cardiac hypertrophy and heart failure ( 46 , 47 ). Hypertrophic stress increases HAT activity and histone acetylation, as p300 is regulated by several proteins, including ERK1/2, Akt, and Cdk9 ( 3 ). However, for HATs such as GCN5, CBP, and PCAF, the relationship with histone acetylation is unclear, although an association between cardiac hypertrophy and heart failure has been reported ( 48 50 ).Curcumin, a natural product, inhibits histone acetylation by blocking the HAT activity of p300, thereby improving cardiomyocyte hypertrophy and HF ( 32 ).…”
Section: Histone Acetyltransferase In Heart Diseasementioning
confidence: 99%
See 2 more Smart Citations